Biology of botryosphaeria dothidea and sphaeropsis sapinea as endophytes of eucalypts and pines in South Africa - Smith, Hendrik (University of the Free State, 2001)
English: Botryosphaeria dothidea and Sphaeropsis sapinea both very important pathogens in the South African forestry context. These fungi are well established in the country and contribute substantially to annual losses incurred. Currently very little can be done to control the fungi and the damage they cause. The understanding of their respective disease etiologies is thus of great importance to develop relevant counter measures. The overall aim of this dissertation was to investigate various poorly understood aspects of these two fungi and to try and relate the results to practical contributions towards controlling the impact the two pathogens have. Studies have been conducted during the course of five years and each study represents an independent research investigation. The introductory chapter presents a review of the literature pertaining to all aspects of biology, history and taxonomy of B. dothidea and S. sapinea. The two fungi are clearly very similar in all these aspects and perhaps the only clear difference is that S. sapinea is restricted to pines in South Africa. Many other similarities and some differences between these two important pathogens are highlighted and many of these have provided the background for further investigations. In chapter two the presence of B. dothidea and S. sapinea lS demonstrated as symptomless endophytes in healthy, pine and eucalypt tissue. Botryosphaeria dothidea was found to be common in all the Eucalyptus spp. tested, occurring at high percentages in symptomless leaves of Eucalptus smithii, E. camaldulensis, E. grandis and E. nitens. Sphaeropsis sapinea was, in contrast, only present in young, green Pinus patuIa and P. radiata cones, but virtually absent from the cones of P. elliottii and P. taeda. Botryosphaeria dothidea is associated with die-back and canker diseases of eucalypts in South Africa. Despite this fact, little is known about the infection process. The fungus is known to occur endophytically in leaves of various Eucalyptus species in South Africa. In chapter three I consider the ability of B. dothidea to infect apparently healthy Eucalyptus leaves and the subsequent location and structure of these infections once inside leaf tissue. Scanning electron microscopy revealed that conidia of B. dothidea can infect healthy leaves through stomata. These infections ultimately reside amongst mesophyll cells and constitute a number of individual infections per leaf. Two morphologically similar fungi are associated with die-back and canker of eucalypts in South Africa. The one was identified as part of the Botryosphaeria dothidea-complex. In chapter four, the identity of the second fungus was determined by comparing morphology, pathogenicity and DNA sequence analysis of isolates of both taxa. Based on results obtained, Botryosphaeria eucalyptorum, and its anamorph Fusicoccum eucalyptorum, are described as a new species. I found that the teleomorph is morphologically similar to other taxa in the B. dothidea-complex, but conidial characteristics of the anamorph are distinct, as well as the sequences of the nrDNA internal transcribed spaeers ITS 1 and ITS2. As is the case with B. doth idea , the fungus is pathogenic to Eucalyptus, there do not, however, appear to be differences in pathogenicity between the two. Sphaeropsis sapinea is the most important pathogen of pines in South Africa. The fungus, which reproduces only asexually, occurs only on exotic pines. In chapter five, I investigated the diversity of the S. sapinea population in South Africa and compared it with a population from Northern Sumatra. Both populations were obtained from exotic P. patuIa plantations. The phenotypic diversity of these populations was assessed using vegetative compatibility tests. The percentage maximum genotypic diversity, based on Stoddard and Taylor's index, for the South African population was much higher than the Northern Sumatran population, thus indicating that the South African S. sapinea population was more diverse than the Northern Sumatran population. These results support the hypothesis that the population of S. sapinea in South Africa has been introduced from various parts of the world, during the last century. In chapter six, I investigated the role that latent S. sapinea infections in seed cones of P. patuIa, play in post-hail associated die-back. Pinus patuIa seed cones were found to be infected during the second year of development, with extensive colonization only occurring m the third year when cones mature, prior to seed discharge. Vegetative compatibility tests revealed that the presence of S. sapinea in individual third year seed cones is confined to a single genetic entity. Sphaeropsis sapinea colonisation of third year seed cones thus, apparently results from a single successful infection per cone. The probable role of latent infections by S. sapinea indicated that tree age and by implication, increased numbers of attached seed cones, contributes to more severe die-back after hail damage. The control of damage caused by S. sapinea is highly dependant on a dynamic hybridisation programme. Alternative species of pines is thus constantly evaluated for potential. In chapter seven, 65 families representing both the northern and southern populations of P. greggii were evaluated for their tolerance to infection and subsequent die-back caused by S. sapinea. Families were evaluated following natural infection after hail damage, as well as by artificial inoculation. Variation in tolerance occurred and was highly significant between the two provenances, with the northern provenance proving to be very tolerant. Pinus greggii trees of the southern provenances were comparable with P. patula. The potential of the families from northern origins has to be investigated further. Cultures of Cytospora isolated from Eucalyptus trees in South Africa, Congo, Thailand, Venezuela, Mexico, Uganda and Australia, as well as Cytospora-like isolates from Indonesia were compared in chapter eight. Comparisons were based on the homology of the internal transcribed spaeer regions and the 5.8S ribosomal DNA of the nuclear ribosomal DNA repeat unit. Isolates clustered into at least three unrelated groupings, with a fourth grouping that included isolates that morphologically resembled Cytospora. Results from this chapter indicated that the current description of Valsa ceratosperma encompasses several distinctly different species and needs to be further refined. Botryosphaeria dothidea and S. sapinea are two of the most important pathogens of eucalypts and pines in South Africa. The fact that they exist as symptom less endophytes in trees has added a fascinating aspect to our understanding of their role in tree diseases. In the past, they have generally been considered to be wound infecting opportunistic fungi. Results of these studies have shown that this is not so and that they are clearly able to infect healthy trees. They are unlikely to be able to infect dead or moribund tissue. The investigations presented in this dissertation have added considerable knowledge to our understanding of B. dothidea and S. sapinea and will also promote efforts to reduce disease caused by them. However, there are many questions that remain to be answered pertaining to them and it is my hope that this study will provide a foundation and stimulus for further work.

Afrikaans: Botryosphaeria dothidea en Sphaeropsis sapinea is albei baie belangrike patogene vir die Suid Afrikaanse bosbou industrie. Hierdie fungi is lank gevestig in die land en dra in 'n groot mate by tot jaarlikse verliese vir die bosbou industrie. Huidiglik is daar baie min wat gedoen kan word om hierdie patogene of die skade wat hulle aanrig te beheer of te beperk. Dit is dus uiters belangrik dat ons hul siekte ontwikkeling verstaan sodat relevante beheer of bestuurs praktyke daar gestel kan word. Die oorkoepelende doel van hierdie studie was dus om aandag te gee aan verskeie aspekte van hierdie twee patogene, om sodoende 'n bydrae te maak tot die praktiese bekamping van skade deur hulle aangerig. Studies was oor 'n vyf jaar tydperk en elke hoofstuk verteenwoordig 'n onafhanklike navorsings projek. Die inleidende hoofstuk is 'n oorsig van die relevante literatuur met betrekking tot die biologie, geskiedenis en taksonomie van B. dothidea en S. sapinea. Die twee fungi is baie naby vervant en kom ooreen in baie aspekte, met dalk die enigste duidelike verskil, die feit dat S. sapinea alleenlik op denne in Suid Afrika voorkom. Baie ander ooreenkomste en verskille tussen die twee belangrike patogene word dus uitgelig en skep dus ook die basis vir verdere navorsing. In hoofstuk twee demonstreer ek die voorkoms van B. dothidea en S. sapinea as simptoomlose endofiete in gesonde bloekom en denne weefsel. Botryosphaeria dothidea het algemeen voorgekom in die gesonde blare van al die Eucalyptus spp. wat getoets was, naamlik Eucalptus smithii, E. camaldulensis, E. grandis en E. nitens. Sphaeropsis sapinea was, daarenteen, slegs gevind in jong, groen këels van Pinus patuIa en P. radiata maar het so te sê ontbreek in die këels van P. elliottii en P. taeda. Botryosphaeria dothidea word geassosieer met terugsterwing en kanker formasie van bloekoms in Suid Afrika. Afgesien van hierdie feit is daar baie min bekend oor die meganisme van infeksie. Die fungus is bekend dat dit voorkom as endofiet in die blare van verskeie Eucalyptus spesies in Suid Afrika. In hoofstuk drie, kyk ek dus na die vermoë van B. dothidea om gesonde blare te infekteer en ook na die lokasie van die tallie in blaar weefsel na infeksie. Skandeer electron mikroskopie is gebruik om vas te stel dat konidia van B. dothidea wel gesonde blare deur huidmondjies kan infekteer. Hierdie infeksies oorleef dan tussen mesofiel selle en die teenwoordigheid van die fungus in blare was die gevolg van veelvuldige infeksies in elke blaar. Twee mofhologies naverwante fungi word geassosieer met terugsterwing en kanker formasie van bloekoms in Suid Afrika. Die een is geidentifiseer as lid van die Botryosphaeria dothidea-kompleks. In hoofstuk vier, word die identiteit van die ander fungus bepaal met die hulp van vergelykings in morfologie, patogenisiteit en DNA opeenvolging analise met isolate van beide taksa. Gebaseer op die resultate word Botryosphaeria eucalyptorum en die anamorf Fusicoccum eucalyptorum as 'n nuwe spesie beskryf. Die teleomorf was morfologies baie naby verwant aan ander taksa in die B. dothidea-kompleks, met die verskille sover dit konidium karakter trekke, die unieke anamorf en die veskille in basispaar opeenvolging van die nrDNA interne getranskibeerde spasies ITS 1 en ITS2. Soos met B. dothidea, is die nuwe fungus ook patogenies op Eucalyptus maar dit blyk dat daar wel verskille in patogenisiteit bestaan. Sphaeropsis sapinea is die ekonomies mees belangrike patogeen van denne in Suid Afrika. Die fungus kom slegs op eksotiese denne voor en reproduseer slegs ongeslagtelik. In hoofstuk vyf onsersoek ek die populasie diversiteit van S. sapinea in Suid Afrika en vergelyk dit met 'n populasie van Noordelike Sumatra. Beide populasies is versamel in eksotiese P. patuia plantasies. Die fenotiepiese diversiteit van hierdie populasies is bepaal deur van vegetatiewe vereenigbaarheids studies gebruik te maak. Die persentasie maksimum genotiepeise deversiteit, gebaseer op Stoddard en Taylor se indeks, het getoon dat die Suid Afrikaanse populasie baie meer divers is as die Noord Sumatra populasie. Hierdie resultate ondersteun die hipotese dat die populasie van S. sapinea in Suid Afrika die land binne gebring was vanuit verskeie ander dele van die wêreld gedurende die afgelope eeu. In hoofstuk ses, bestudeer ek die rol wat latente infeksies in këels, deur S. sapinea, speel in die siekte ontwikkeling na hael skade. Pinus patuia këels word in die tweede jaar geinfekteer, maar word eers in die derde jaar gekoloniseer voordat saad vrystelling plaasvind. Vegetatiewe vereenigbaarheids toetse het bewys dat S. sapinea in individuele këels voorkaom as 'n enkele genetiese entitieit. Dus lyk dit asof die kolonisasie van drie jaar oue këels deur S. sapinea onstaan as 'n enkele infeksie per këel. Die beheer van skade veroorsaak deur S. sapinea is afhanklik van 'n dinamiese teelprogram. Alternatiewe spesies van denne word voordurend geevalueer vir potensiaal. In hoofstuk sewe word 65 famielies van die noordelike en suidelike populasies van P. greggii uit Meksiko geevalueer vir moontlike weerstand teen S. sapinea. Famielies was geevalueer deur van natuurlike infeksies na hael en van kunsmatige inokulasies gebruik te maak. Famieleis van die noordelike populasie was baie meer weerstandbiedend en dus word hul potensiaal verder ondersoek. Botryosphaeria dothidea en S. sapinea is twee baie belangrike patogene vir die bosbou bedryf in Suid Afrika. Die feit dat beide kan voortbestaan as simptoomlose endofiete het 'n baie interressante faset van hul biologie bloot gelê. In die verlede was beide hoofsaaklik geken as patogene wat slegs wonde kan infekteer. Resulate van hierdie studies het egter bewys dat hulle ook in staat is om gesonde weefsels te infekteer. Dit lyk egter ook asof beide nie in staat sou wees om dooie material te infekteer nie. Die resulate wat hier voorgehou word het baie bygedra tot ons kennis rondom B. dothidea en S. sapinea, en sal dien om verdere navorsing te stimuleer.
Keywords: Botryosphaeria dothidea; Sphaeropsis sapinea; Eucalyptus; Pinus; Endophyte; Population genetics; Vegetative compatibility; Sequencing; Eucalyptus -- South Africa -- Diseases and pests; Fungal diseases of plants -- South Africa; Thesis (Ph.D. (Microbiology and Biochemistry))--University of the Free State, 2001